Effects of cognitive entry characteristics and gender on students' cognitive achievement in bearing. (2008)
There are evidences that showed that most Nigerian Students tend to dread and fail mathematics. Bloom (1981) Bloom theory of learning (Based on mastery learning studies) tends to suggest that this needs not be, he asserts that if students enter into learning situation with adequate level of Cognitive Entry Characteristics (CEC), most students are assure of high degree of learning. Under this situation according to him aptitude ceases to predict achievement. This study sought to see the application of Bloom's (1981) theory to learning of bearing under an Experimental 'setting. This study used a quasi experimental research type to find the effect of CEC on students' Cognitive achievements in bearing. Two hundred and twenty seven SS2 students were involved. The sample was drawn using multi-stage sampling technique to select tvvo public co-educational secondary schools each, from two selected Local Government reas in Ibadan Metropolis. The instruments used for data collection were the,' Mathematics Achievement Test, with reliability coefficients of 0.75 and Diagnostic Tests. The data collected were analysed using ANCOVA to find the effect ofCEC and gender on students' cognitive achievement. The study found out that at 0.05 level of significance, CEC and gender with f-ratios of 79.832 and 7.045 respectively have significant main effects on Students .Cognitive achievement in bearing. CEC and gender however, have no significant interaction effect on cognitive achievement of students in bearing. The results support the theory of Bloom (1981) that students with adequate level of CEC tend to achieve high degree of learning. This tends to suggest that failure rate in mathematics can be reduced if teachers ensure that students come into learning situation with necessary CEC.